Gestational diabetes mellitus increases the detection rate and the number of oral bacteria in pregnant women. Issue 11 (March 2019) - Yao, Han; Xu, Dan; Zhu, Zhichao; Wang, Guoyun
Abstract : Abstract: In the present study, we aimed to investigate the association between gestational diabetes mellitus (GDM) and the oral microbial imbalance in the second trimester of pregnancy. Three hundred thirtyone women in the second trimester of pregnancy who underwent prenatal examinations at the Third Affiliated Hospital of Soochow University from February 2018 to August 2018 were included in this study. Personal parameters including the age, education level, and body mass index (BMI) at 28 weeks of gestation were recorded. Gestational diabetes mellitus (GDM) was diagnosed according to the Standards of Medical Care in Diabetes-2011 recommended by American Diabetes Association (ADA). After the significant difference of each parameter was erased by a propensity-score matched (PSM) analysis at a 1:1 ratio, the oral health conditions and the oral flora in pregnant women with GDM were compared with those in nondiabetic pregnant women. Our data demonstrated that 65 of the 331 pregnant women (19.6%) were diagnosed with GDM. Results from the matched data including 59 matched pairs of pregnant women showed that the gingival index (GI), plaque index (PI), tooth mobility degree (TMD), probing depth (PD), and bleeding on probing (BOP) of pregnant women with GDM were higher or more severe than those of nondiabetic pregnant women ( P < .05). The detection rate of tuberculosis bacilli, Black-pigmented bacteria, and Capnocytophaga in pregnant women with GDM was higher than those in nondiabetic pregnant women ( P = .000, P = .026, and P = .030, respectively). In addition, pregnant women with GDM had fewer oral streptococci ( P = .000) and lactobacilli ( P = .000) and more oral anaerobic bacteria ( P = .000), tuberculosis bacilli ( P = .000), Black-pigmented bacteria ( P = .007), Capnocytophaga ( P = .000), and actinomycetes ( P = .000). The detection rate and the number of oral bacteria in pregnant women with GDM were higher than those in nondiabetic pregnant women in the second trimester of pregnancy.